Timosaponin AIII Induces G2/M Arrest and Apoptosis in Breast Cancer by Activating the ATM/Chk2 and p38 MAPK Signaling Pathways - Zhang, Minjie; Qu, Jiaxi; Gao, Zhiwei; Qi, Qi; Yin, Hong; Zhu, Ling; Wu, Yichen; Liu, Wei; Yang, Jian; Huang, Xuefeng (Frontiers in Pharmacology, 2021)
Timosaponin AIII (TAIII), a steroidal saponin, exerts potent anti-tumor activity in various cancers, especially breast cancer. However, the concrete molecular mechanisms of TAIII against breast cancer are still unclear. Here, we find that TAIII triggers DNA damage, leads to G2/M arrest, and ultimately induces apoptosis in breast cancer both in vitro and in vivo. TAIII induced G2/M phase arrest and apoptosis in MDA-MB-231 and MCF7 cells accompanied with down-regulation of CyclinB1, Cdc2 and Cdc25C. Further data showed that the ATM/Chk2 and p38 pathways were activated representing by up-regulated levels of p-H2A.X and p-p38, which indicated an induction of DNA damage by TAIII, leading to cell cycle arrest and apoptosis. The effects of TAIII were further confirmed by employing inhibitors of ATM and p38 pathways. In vivo, TAIII suppressed the growth of subcutaneous xenograft tumor without obvious toxicity, which indicated by Ki67 and TUNEL analysis. Data also showed that TAIII stimulated the ATM/Chk2 and p38 MAPK pathways in vivo, which in consistent with the effects in vitro. Hence, our data demonstrate that TAIII triggers DNA damage and activates ATM/Chk2 and p38 MAPK pathways, and then induces G2/M phase arrest and apoptosis in breast cancer, which provide theoretical evidence for TAIII utilized as drug against breast cancer.